PPARγ Gene Polymorphisms, Metabolic Disorders, and Coronary Artery Disease - Song, Yongyan; Li, Shujin; He, Chuan (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Being activated by endogenous and exogenous ligands, nuclear receptor peroxisome proliferator-activated receptor gamma (PPARγ) enhances insulin sensitivity, promotes adipocyte differentiation, stimulates adipogenesis, and has the properties of anti-inflammation and anti-oxidation, anti-atherosclerosis. Human PPARγ gene (PPARG) contains thousands of polymorphic loci, among them two polymorphisms (rs10865710 and rs7649970) in the promoter region and two polymorphisms (rs1801282 and rs3856806) in the exon region were widely reported to be significantly associated with coronary artery disease (CAD). In mechanisms, the associations between polymorphisms in PPARG and CAD risk are mainly mediated by cardiometabolic risk factors such as dyslipidemia, hypertension, obesity and chronic inflammation.